The Arab Position on The Armenian Massacres During The Ottoman Empire (Journal of the College of Basic Education, 2025)
Armenians were subjected to a systematic genocide and expulsion in the lands of the Ottoman Empire during the First World War at the hands of the government of the Union and Progressive Society, which worked to implement the policy of Turkification by force. The Ottoman government justified its actions by claiming that Armenians were carrying out attacks on Ottoman forces and villages at the instigation of the Russian government, and that some Armenians were demanding reforms that would improve their situation in the Ottoman state and make them equal to other peoples. Many historians agree that the beginning of the real genocide was on April 24, 1915, when they were displaced from their homes and regions to places far from the capital, Istanbul, on this day, the Ottoman government gathered and arrested hundreds of Armenian intellectuals, notables, women, children and Armenian men, arrested them and deported them from the capital, where most of them died. They were forced to walk during the deportation on deadly roads, after which they were killed, looted and plundered, especially in 1915 and 1916, and hundreds of thousands of unarmed Armenians were killed as a result of these events.